Social representations: a theoretical approach in health - doi:10.5020/18061230.2011.p80 - Bittencourt, Isaiane Santos (2012)
Objective: To present the theory of social representations, placing its epistemology and knowing the basic concepts of its approach as a structural unit of knowledge for health studies. Justification: The use of this theory comes from the need to understand social events under the lens of the meanings constructed by the community. Data Synthesis: This was a descriptive study of literature review, which used as a source of data collection the classical authors of social representations supported by articles from electronic search at Virtual Health Library (VHL). The definition and discussion of collected data enabled to introduce two themes, versed on the history and epistemology of representations and on the structural approach of representations in health studies. Conclusion: This review allowed highlight the importance of locating the objects of study with regard to contextual issues of individual and collective histories, valuing the plurality of relations, to come closer to reality that is represented by the subjects.